THE WAVE & PARTICLE DUALITY- PHOTON AND ELEMENTARY-PARTICLES ORIGINATION - Giorgallides, Marcos (IJRDO-Journal of Applied Science, 2020)
Distance is the Quantum of E-Geometry , while Material-point is the Quantum in Physics and inMaterial-Geometry which is the composition of Opposites and are the Elements in Chemistry andPhysics . As in Algebra Zero ,0, is the Master-key number for all Positive and Negative numbers ,because their sum and multiplication is zero , and the same on coordinate-system ± axes pass from zeroThe Rolling of Positive ⊕ , constituent on the Negative ⊝ , constituent , creates the Neutral MaterialPoint which Equilibrium . Spin